Effect of pre‐existing diseases on COVID‐19 infection and role of new sensors and biomaterials for its detection and treatment. Issue 1 (16th November 2020) - Singh, Angaraj; Kumar, Manoj; Kumar Dubey, Ashutosh
Abstract: The entire world is suffering from a new type of viral disease, occurred by severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2). The present article briefly discussed the genome sequencing and interaction of host cells with SARS‐CoV‐2. The influence of pre‐existing diseases such as diabetes, heart disease and age of the patients on COVID‐19 infection is reviewed. The possible treatments of SARS‐CoV‐2 including antiviral drugs, Chinese traditional treatment and plasma therapy are elaborately discussed. The proper vaccine for COVID‐19 is not available till date. However, the trials of pre‐existing antiviral vaccines such as, chloroquine/hydroxychloroquine, remdesivir, ritonavir and lopinavir and their consequences are briefly presented. Further, the importance of new materials and devices for the detection and treatment of COVID‐19 has also been reviewed. The polymerase chain reaction (PCR)‐based, and non‐PCR‐based devices are used for the detection of COVID‐19 infection. The non‐PCR‐based devices provide rapid results as compared to PCR‐based devices.